(untitled) (Research, Society and Development, 2022)
Objective: To analyze the profile of the student body of a private college in the city of Belém/PA, regarding the indiscriminate use of antibiotics and bacterial resistance. Methodology: A descriptive, quantitative, and qualitative research was carried out, which made it possible to analyze the profile of the 207 participants. Anonymously, without collecting personal data, the participation of students from pharmacy, nursing, physiotherapy, biomedicine, law, administration, and engineering courses was obtained, with data collected through a questionnaire prepared through the Google Forms platform. Results: In general, most students had knowledge about the irrational use of antibiotics and bacterial resistance, claiming to be in accordance with the RDC 20/2011 legislation, however most reported using antibiotic therapy empirically, without medical advice. The other answers obtained to the applied questions point to the same line of results, where most of the public under study is aware of the importance of complying with an antimicrobial treatment for the correct time and are in accordance with the need for the medical prescription to purchase this medication. drug class. Conclusion: The research showed positive results regarding the degree of knowledge of academics about the topic under discussion, but in contradiction, most respondents reported self-medication practices. With this, it was possible to draw a profile of informed individuals, but not yet sufficiently aware of the dimension of the growing public health problem which has become the spread of multidrug-resistant bacterial strains.